Hemoglobin levels during the first trimester of pregnancy are associated with the risk of gestational diabetes mellitus, pre-eclampsia and preterm birth in Chinese women: a retrospective study - Chen Wang; Li Lin; Rina Su; Weiwei Zhu; Yumei Wei; Jie Yan; Hui Feng; Boya Li; Shuang Li; Huixia Yang (BMC, 2018)
Abstract Background Hemoglobin (Hb) measurement is a standard test among pregnant women during the first perinatal visit that is used to evaluate physical status and anemia. However, studies focusing on Hb levels and pregnancy outcomes are scarce. This study aimed to determine whether Hb levels in early pregnancy were associated with the risk of gestational diabetes mellitus (GDM), pre-eclampsia (PE) and preterm birth. Methods A hospital-based retrospective study was conducted among 21,577 singleton, non-smoking pregnancies between June 2013 and January 2015. The demographic data and medical information of each participant were collected individually through questionnaires and patient medical records. Odds ratios were generated using a multivariate logistic regression analysis to evaluate the relative risk of GDM, PE and preterm birth continuously and across different hemoglobin ranges in the overall population and in women from different pre-pregnancy body mass index (BMI) categories, respectively. The level of statistical significance was set at 0.05. Results (1) For women who were underweight, normal-weight, overweight and obese, early pregnancy Hb levels were 127.8 ± 10.1 g/L, 129.6 ± 9.7 g/L, 132.2 ± 9.5 g/L and 133.4 ± 9.4 g/L, respectively. (2) Women with GDM and PE had significantly increased Hb levels during early pregnancy compared with controls, whereas women with preterm birth processed significantly decreased Hb levels. (3) After adjusting for confounders, the risks for GDM and PE increased with high maternal Hb (OR: 1.27 for Hb 130-149; OR: 2.06 for Hb ≥ 150 g/L), and the risk for preterm birth decreased with high maternal Hb (OR: 1.30 for Hb 130-149; OR: 2.38 for Hb ≥ 150 g/L) and increased with low maternal Hb (OR: 1.41 for Hb <  110 g/L). Among women whose BMI was < 24 kg/m2, high GDM (OR: 1.27 for Hb 130-149; OR: 1.84 for Hb ≥ 150 g/L) and low preterm rates (OR: 0.77 for Hb 130-149; OR: 0.23 for Hb ≥ 150 g/L) were observed with high Hb, whereas in women whose BMI was ≥24 kg/m2, only high GDM rates were observed with Hb > 150 g/L (OR: 2.33). Conclusion These findings suggest that Hb levels during early pregnancy play a role in predicting the risk of GDM, PE and preterm birth.